PERAN KEPALA DESA DI LIHAT DARI ASPEK PANUTAN DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR DESA WIRANG KECAMATAN HARUAI KABUPATEN TABALONG (JAPB, 2022)
The role of leadership in improving employee performance is one of the essential elements in an organization where the organization is a place for humans to gather and work together to achieve a specific goal. The village head is one of the crucial factors in running the government, which is tasked with regulating employees and improving the performance of their employees; a village head must be able to mingle with his employees, and the goal is to be able to read the characteristics of each employee and understand how to treat his employees. The purpose of this study was to determine the significance of the role of the village head from the aspect of role models in improving employee performance at the Wirang Village Office, Haruai District, Tabalong Regency. This study uses a descriptive-qualitative research method, with data collection methods using: interviews and documentation. Data analysis in this study uses an interactive model developed by Miles & Huberman (Sugiyono, 2013): data reduction, data presentation, and conclusion. Informants in this study amounted to 8 people, namely Village Office Apparatus & 1 Head of RT. The results of this study indicate that the role of the village head, seen from the aspect of role models in improving employee performance at the Wirang Village Office, Haruai District, Tabalong Regency, is included in the excellent category. Keywords: Role, Village Head, Improving Employee Performance